(untitled) (Journal of Philosophy Culture and Political Science, 2018)
The paper presents research on the spiritual culture of Otrar civilization. The progressive impact of the Silk Road on the social and cultural development of Otrar and other cities of Kazakhstan was shown. The historical and philosophical aspects of Otrar phenomenon - a great Orient thinker Abu Nasir Al-Farabi were discussed.